The Issues of Justice and the Right of Access to Justice in Vietnamese Law - Thai, Pham Hong (VNU Journal of Science: Legal Studies; Vol 36 No 1, 2020)
Justice and the right to access to justice are fundamental issues in the law of every country, which are also vast and complex content. The article analyzes the provisions relating to justice and the right to access to justice in Vietnamese law from the feudal period up to present, especially in basic legal document such as the Constitution, the Criminal Code, and the Procedural Criminal Code, etc. The author argues that justice and the right to access to justice have been adopted in Vietnamese law since the feudal period. The provisions of justice and the right to access to justice in current laws of Vietnam are promoted from the related provisions in the feudal law, along with the acquisition of the progressive values ​​of mankind in this area. Keywords: Justice, the right to justice, law, Vietnam. References: [1] Institute of Linguistics (2000), Vietnamese Dictionary, Da Nang Publishing House, p.208. [2] Vietnamese Dictionary (1999), Bach Khoa Publishing House, p.210. [3] Maison du Droit Vietnamien-Français (2009), Dictionnaire du Droit Français-Vietnamien, éditeur de l'encyclopédie, p.494. [4] Vietnamese Dictionary (edited by Nguyen Nhu Y), the Publisher of Culture and Information. 1999. p. 1757. [5] Russian Ozhegov Dictionary, M., 1949. [6] Dai Viet Su Ky toan thu, Volume 1, Publisher of Social Sciences. 1998, p.205. [7] History of State and Law of Vietnam, Publisher of National University, 2017, p. 108. [8] Translated version by Nguyen Ngoc Nhuan and Nguyen Ta Nhi, Justice Publisher, 2013. [9] Le trieu quan che , translated by Pham Van Lieu, the Publisher of Culture and Information. Ha Noi, 1997, p.13.